2017
DOI: 10.1039/c7sc01732d
|View full text |Cite
|
Sign up to set email alerts
|

Pivalophenone imine as a benzonitrile surrogate for directed C–H bond functionalization

Abstract: Pivalophenone N–H imine undergoes facile directed C–H functionalization and subsequent iminyl radical fragmentation, thus efficiently affording ortho-functionalized benzonitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 76 publications
1
28
0
1
Order By: Relevance
“…We previously demonstrated that ortho ‐arylated and alkylated pivalophenone N−H imines efficiently undergo fragmentation of the pivaloyl imine moiety into a cyano group under peroxide photolysis or aerobic copper catalysis . The same transformation proved feasible for the methylated products, and conversion of 3 c into the ortho ‐methylated aryl nitrile 4 was achieved in good yield under aerobic copper catalysis (Scheme ) …”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…We previously demonstrated that ortho ‐arylated and alkylated pivalophenone N−H imines efficiently undergo fragmentation of the pivaloyl imine moiety into a cyano group under peroxide photolysis or aerobic copper catalysis . The same transformation proved feasible for the methylated products, and conversion of 3 c into the ortho ‐methylated aryl nitrile 4 was achieved in good yield under aerobic copper catalysis (Scheme ) …”
Section: Methodsmentioning
confidence: 73%
“…Recently, we have demonstrated that pivaloyl N−H imine serves as an excellent directing group for cobalt‐catalyzed ortho C−H functionalization reactions such as hydroarylation to alkenes and alkylation/arylation with the corresponding organic halides . The imine functionality can be readily transformed into a cyano group, thus allowing facile preparation of ortho ‐functionalized benzonitriles . Given this background and other reports on transition‐metal‐catalyzed, N−H imine‐directed C−H functionalization, we became interested in the competence of pivaloyl N−H imine as a monodentate directing group for the iron‐catalyzed C−H/C−M coupling manifold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, fragmentations of cyclic iminyl radicals have been less studied. These processes, which until recently have been observed mainly in the context of nitrile translocations, produce a synthetically useful nitrile tethered to an alkyl radical. However, rapid reduction of the alkyl radical by a hydrogen atom donor that is often present in the reaction mixture (e.g., Bu 3 SnH) has precluded further functionalization.…”
Section: Methodsmentioning
confidence: 99%
“…Dieses Verfahren wurde weiter auf die Umsetzung von Pivalophenon-N-H-Iminen ausgeweitet, die sich als hervorragende Benzonitrilsurrogate fürdirigierte C-H-Alkylierungen erwiesen, bei denen die entsprechenden Benzonitrile in einem Folgeschritt entweder durch Bestrahlung in Gegenwart eines Peroxids oder durch Reaktion mit einer katalytischen Mengen an Kupfer(II)-acetat unter aeroben Bedingungen hergestellt wurden. [67] Weitere Untersuchungen in der Gruppe von Ackermann zur rutheniumkatalysierten Alkylierung von Iminen gipfelten in der Entwicklung einer hochregioselektiven meta-Alkylierung mit sekundären und tertiären Alkylbromiden (Schema 12). [68] Mit einem Katalysesystem, das dem mit primären Alkylbromiden verwendeten stark ähnelte,e rfolgte eine saubere meta-selektive Alkylierung von TMP-Iminen.…”
Section: Alkylierung Von Aryliminen Mit Alkylhalogenidenunclassified